"De smaa graa". Livshistorier - vandrebøger. - Mortensen, Morten (Forum for Idræt, 2006)
Artiklen diskutterer analyse- og forskningsmetode i forbindelse med idrætsliv og idrætshistorie. Det grundtvigianske højskoleliv og brevsamlinger, såkaldet vandrebøger, bliver anvendt som eksempler på kilderstudier. Morten Mortensen: »The small grey.« Life history and travelling books Many attempts from sport historians to write total life history has failed due to inappropriate sources. The result instead has been traditional historical biographies, where the personal and intimate history of central political agents is employed for explanations of the activities of the agent in the larger political history. On the other hand, there is a lack of total life history of so called ordinary and more, plain agents, that can be unfolded in the smaller history (the history of every day life). The use of other types of sources can be a way out of this scientific backwater. The article describes and introduces ‘travelling books’ (vandrebøger) from the milieu of Grundtvigianism as an example of a useful source to highlight the relation between the personal history in the private sphere and the popular sport movement. Sources like the travelling books can be employed for analyses of the meeting between the every day life and the ideals of the popular movements, between the large and the small history.